Pengaruh Informasi Non Keuangan terhadap Keputusan Investasi di Bursa Efek Indonesia - Alistraja Dison Silalahi; Erlina Erlina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Non-financial information describes the company's future performance, and at the same time illustrates that the company has been managed well. This research was conducted to see whether non-financial information influences investment decisions on the Indonesian stock exchange. The sample technique used in this study was purposive sampling with criteria: investors who started investing in 2015, investors who had a diploma and bachelor's education and investors who invested for three years. The analysis technique in this study is simple linear regression and moderated regression anlysis. Hypothesis testing in this study shows that non-financial information influences investment decisions. Keywords: Non-Financial Information, Investment Decisions and Financial Advisory Recommendations